2004
DOI: 10.1007/s00299-004-0824-9
|View full text |Cite
|
Sign up to set email alerts
|

Plastids and stromules interact with the nucleus and cell membrane in vascular plants

Abstract: The various metabolic activities of plastids require continuous exchange of reactants and products with other organelles of the plant cell. Physical interactions between plastids and other organelles might therefore enhance the efficiency of plant metabolism. We have observed a close apposition of plastids and nuclei in various organs of Nicotiana tabacum and Arabidopsis thaliana. In hypocotyl epidermal cells, plastids and stromules, stroma-filled tubular extensions of the plastid envelope membrane, were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 22 publications
3
107
2
1
Order By: Relevance
“…36,37 Furthermore, stromules have been shown to extend into the cytoplasm, generally, in a rather straight line. 34,35 This was not found in the present material. The data suggest, therefore, that the plastids did not form protrusions of any type, including stromules.…”
Section: O N O T D I S T R I B U T Econtrasting
confidence: 52%
See 1 more Smart Citation
“…36,37 Furthermore, stromules have been shown to extend into the cytoplasm, generally, in a rather straight line. 34,35 This was not found in the present material. The data suggest, therefore, that the plastids did not form protrusions of any type, including stromules.…”
Section: O N O T D I S T R I B U T Econtrasting
confidence: 52%
“…They can extend far into the cytoplasm, are able to interconnect plastids and allow the transfer of protein complexes as large as 550 kDa. 33 Using light microscopy the stromule diameter varied between 0.3 and 0.8 μm 34,35 whilst TEM showed stromules of about 0.4 μm diameter. 37 The means and standard deviation of the diameter of the thin plastid strands …”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…In different tissues of tobacco and Arabidopsis, stromules interact with the nucleus, the plasma membrane and mitochondria. They possibly support transfers such as DAG, PC or DGDG transfers, although this role of stromules has never been demonstrated [89,90]. Other plastid envelope structures have been visualised to resemble myelin.…”
Section: Pe Biosynthesis In Mitochondria Occurs By Decarboxylation Ofmentioning
confidence: 99%
“…SFs were similar to those previously reported for Arabidopsis (Holzinger et al, 2008;Newell et al, 2012). Because hypocotyl epidermal cells were used to study stromules in numerous previous publications (Hanson and Sattarzadeh, 2013;Kwok and Hanson, 2004;Holzinger, Kwok et al, 2008;Newell et al, 2012), we selected these cells to evaluate the effect of different treatments involving low phosphate, sugars, or strigolactones.…”
Section: Different Stromule Frequency In Different Cell Typesmentioning
confidence: 62%
“…Thus, stromules give a large increase in the potential contact between plastid and other cell compartments. Indeed, stromules seem to be intercalated between ER membranes (Schattat et al, 2011a(Schattat et al, , 2011b, but stromules have also been observed in infoldings of the nuclear envelope (Kwok and Hanson, 2004). In a high-throughput screen of cDNA-GFP fusions, many proteins were found to be localized to the stroma of chloroplasts, but not all of them were also localized to stromules (Escobar et al, 2003).…”
mentioning
confidence: 99%